CAN WE TALK ABOUT RACISIM IN EAP? (BALEAP Journal of Research and Practice, 2025)
‘Can we talk about racism in EAP?’ reflects on the Community Session of the same name at the BALEAP 2023 Biennial Conference. Using JPB Gerald’s talk ‘Bad at English’ (2021) as a stimulus, the session invited discussion on the challenges and benefits of integrating anti-racist pedagogy into EAP curricula. Questions explored included the extent to which ideas around linguistic deficit are linked to racism, the potentially compromised role of EAP practitioners when adopting a raciolinguistic perspective, and to extent to which raciolinguistic theories developed in a US context are more broadly applicable. Reflections from the session reiterated the importance of addressing coloniality and racism in EAP and provided powerful evidence of the session’s impact. However, the discomfort and resistance some educators expressed when these issues were raised highlight that much work remains to be done. This write-up contends that EAP and anglophone academia are rooted in the legacies of British and US imperialism and White supremacy, which continue to shape discriminatory policies and practices in language education and perpetuate the dominance of raciolinguistic ideologies such as native-speakerism and monolingualism. It concludes by advocating for EAP educators to embrace the political nature of language education and adopt a raciolinguistic perspective to challenge colonial legacies and work towards dismantling systemic racial and linguistic inequities in EAP and beyond.